Genome sequence of an aichivirus detected in a common pipistrelle bat (Pipistrellus pipistrellus) - Diakoudi G.; Jamnikar-Ciglenecki U.; Lanave G.; Lelli D.; Martella V.; Kuhar U. (Archives of Virology, 2020)
The family Picornaviridae includes important human and animal pathogens that are associated with a wide range of diseases and, in some cases, have zoonotic potential. During epidemiological surveillance of bats, we identified, by next-generation sequencing (NGS) techniques, the presence of picornavirus RNA in a common pipistrelle bat (Pipistrellus pipistrellus). By coupling NGS, primer-walking strategies, and sequence-independent protocols to obtain the sequences of the 5′ and 3′ termini, we reconstructed the genome sequence of picornavirus strain ITA/2017/189/18-155. The genome of the bat picornavirus is 8.2kb in length and encodes a polyprotein of 2462 amino acids. A comparison of polyprotein sequences revealed that this virus is distantly related (65.1% and 70.9% sequence identity at the nucleotide and amino acid level, respectively) to a bat aichivirus identified in 2010. Phylogenetic analysis showed that this picornavirus clustered closely with members of the genus Kobuvirus, which also includes human and animal aichiviruses. The identification of aichiviruses in several animal hosts is providing hints that will lead to an understanding of their origin and evolutionary patterns.